Music training in decolonial, opened and embodied perspectives: experiments in Counterpoint and Ensemble Practices - Fridman, Ana Luisa [UNESP]; Moraes Costa, Rogerio Luiz [UNESP]; Musicoguia (Adaya Press, 2022)
This article brings proposals of two professors in undergraduate music courses, in continuity with initiatives already presented to CIVAE (Costa, & Fridman, 2020). For this edition of the event, reflections and initiatives within Music Counterpoint and Ensemble Practices will be described, in addition to a creative experience involving a musical interaction between the teachers of these disciplines. The article also raise questions about important aspects to rethink the ongoing curricula in Brazilian universities, such as decolonial and non-hierarchical approaches, which value local culture and current issues, in addition to awakening poetic and immersive states of performance from the appreciation of studies involving corporeality and presence in music education and performance environments.
Keywords: music education; decolonial Iniciatives; creative processes; corporeality